The impact of democracy, government ideology, and globalization on social spending in less developed countries. (October 2015) - Ha, Eunyoung
This study examines how democracy, government ideology, and globalization have shaped social expenditures in 67 less developed countries from 1975 to 2005. The empirical results show that more democratic nations spend a greater amount on social security and welfare (SSW), while leftist governments spend more on education. This is because, in most less developed nations, SSW programs disproportionately benefit formal-sector workers, who tend to be the decisive voters in the countries, and education spending helps a broader spectrum of people. The article also examines factors related to globalization and finds that a higher level of external debt is strongly associated with reduced SSW spending, which imposes direct costs and burdens to business. The results in this article provide evidence that, even in less developed countries, political leaders' commitment to social expenditures varies according to their electoral, ideological, and economic interests.